ANALYSIS OF GREENHOUSE VEGETABLE PRODUCTION IN AGRICULR TURAL ORGANIZATIONS OF SARATOV REGION - V. V. Petukhova (Овощи России, 2015)
The general tendencies  of the market development of vegetable crops of protected  ground in the agricultural organizations in the Saratov region over the period of 2005-2011 are described  in the article. Parameters  of productivity; marketability; profitability; structure  of manufacture  and structure of a commodity output; expenses  of work on 1 sq. m and 1 c production on set of the investigated organizations are calculated. The analysis of a condition and tendencies  of development of the vegetable6growing agricultural enterprises  is studied  with use of the basic indicators of descriptive statistics.